TRADITIONAL ECONOMIC PHILANTHROPY: EVIDENCE FROM MADURESE ALTRUISM LOCAL PATTERN - Prasetyono Prasetyono; Yuliana Rakhmawati; Erfan Muhammad; Emi Rahmawati; Ach Fawaiq As’ad (Sosiohumaniora, 2021)
Recently, modern philanthropy practices tends to relate with corporations, organizations, and institutions activities. Meanwhile in some Indonesia’s regions, philanthropy is not always present in that context. Madura is one of the regional that traditionally uses philanthropic patterns in its economic activities as social and cultural traits and custom. Therefore, this research attempt to describe the traditional philanthropy in Madurese. This research uses qualitative perspective and employed Interpretive Phenomenological Analysis (IPA) to gain the local perspective experience and meaning construction in traditional philanthropy through cattle sharing program. Parties involve in this research are the breeders or cattle farmers and local investors. The research found that Madurese traditional economic philanthropy activities are carried out in a cattle sharing practice with local wisdom principle. Madurese local philanthropy pattern has the context of reducing breeding risk or loss if the cattle are sicks or death. These activities seem to be quite helpful in strengthening the helping spirit  and strengthening the local traits and customs economy. Hence, by conducting the value of tolong bi nolong local people tends to practice philanthropic engagement. The future studies could explore more culturally and institutionally structured management to enhance this good practice sustainability.